Clinical researchLung parenchymal involvement and sputum bacteriology in tuberculous pelurisy: correlation with pleural fluid biochemical parameters - Ucar, Ergun; Tozkoparan, Ergun; Gumus, Seyfettin; Deniz, Omer; Ors, Fatih; Bozlar, Ugur; Ciftci, Faruk (Archives of Medical Science, 2009)
Introduction: It has been shown in some studies that a significant proportion of the cases with tuberculous pleurisy may have positive sputum culture for Mycobacterium tuberculosis or associated parenchymal involvement in computed tomography. We aimed to investigate high-resolution computed tomographic (HRCT) findings of lung parenchyma and their correlations with sputum bacteriology, serum and pleural fluid biochemical parameters. Material and methods: A number of thirty-four patients with tuberculous pleurisy were investigated by using HRCT in order to assess the parenchimal involvement giving a profusion score. The sputum culture for M. tuberculosis was also performed. Pleural fluid and adenosine deaminase, (p-ADA) lactate dehydrogenase (p-LDH), protein and albumin levels were quantified and size of the pleural effusion was scored on chest X-ray. Results: Six of 34 (17.6%) patients had positive sputum culture for M. tuberculosis. A significant correlation between HRCT score and p-ADA (rs = 0.634, p < 0.001), p-LDH (rs = 0.548, p = 0.001) levels and size of the pleural effusion (rs = 0.414, p = 0.015) was found. Furthermore, patients with positive M. tuberculosis culture in sputum had significantly elevated p-LDH (1790.7 ±899.4 vs. 955.7 ±383.2 U/l, p = 0.002) and p-ADA (101.8 ±29.8 vs. 67.8 ±17.6 U/l, p = 0.002), larger pleural effusion and HRCT score (p = 0.042 and p < 0.001 respectively). Conclusions: We concluded that degree of inflammation in TP might be affected by simultaneous pulmonary parenchymal changes and sputum bacteriology. It might be suggested that TP might be a different manifestation of pulmonary TB rather than an extra-pulmonary disease.